Work demands, responses, and coping strategies for staff in high-performance sport: a scoping review - Mercer, R. A. J.; Russell, J. L.; Strack, D. S.; Coutts, A. J.; McLean, B. D. (Sports Medicine, 2025)
Background: Understanding the work demands and psychobiological responses of high-performance sport practitioners is important for informing strategies that support and improve staff health, well-being, and performance. Although research in this area has grown, previous reviews have focused on specific aspects of well-being and particular practitioner populations. Currently, no comprehensive reviews summarize all research relating to high-performance sport practitioners. A broad overview could help clarify the work demands and responses of staff in this field. Objectives: This scoping review aims to provide an overview of the literature on staff working in high-performance sport with roles and responsibilities related to athlete operations and/or performance. Using theoretical frameworks to operationally define key concepts, the review maps relevant studies and summarizes findings on work demands, resources, coping strategies, and responses in high-performance sport. Methods: A scoping review was conducted and reported in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR). Searches were performed across three electronic databases, PubMed, PsycINFO, and SPORTDiscus, to identify relevant studies published up to 1 August 2024. The search strategy employed terms related to working in high-performance sport and was structured using the population, exposure, and outcome framework. Studies examining staff working full-time in high-performance sport and assessing work demands, responses, resources, or coping strategies were included. This review was registered with the Open Science Framework (osf.io/br9hm/). Results: Electronic and manual searches identified 124 studies meeting the inclusion criteria. These studies spanned various levels of sport: collegiate (n = 53), professional (n = 24), national/international (n = 13), Olympic/Paralympic (n = 10), mixed levels (n = 14), and "high-performance" or "elite" sport (n = 10). The studies examined coaches (n = 79), medical and performance staff (n = 41), and mixed practitioners (n = 4). Data on countries, competitions, study designs, measurement tools, and theoretical frameworks were reported for each study. Outcomes assessed included responses (n = 24), demands (n = 12), resources and coping (n = 12), and mixed combinations (n = 76), with the most common combinations being "demands, responses, and resources and coping" (n = 23) and "demands and resources and coping" (n = 21). Conclusions: Practitioners in high-performance sport encounter a diverse array of demands, including workload challenges, organizational and structural factors, athlete- and performance-related pressures, and sociocultural factors. These challenges often elicit a range of emotional, psychological, physical, and physiological responses, contributing to persistent issues such as burnout and difficulties in achieving work-life balance. To navigate these challenges, practitioners employ a variety of coping strategies and leverage both personal and organizational resources, highlighting the multifaceted nature of their experiences in these environments. These findings enhance our understanding of how occupational demands and stress affect individuals working in sport and can inform evidence-based strategies to improve coping, organizational support, and overall health, well-being, and performance.